The value of mutual cooperation in the iriban tradition - Ervina Resti Arin; Eta Yuni Lestari (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2023)
The Iriban tradition is a tradition of cleaning irrigation streams (Wangan) sourced from Cenginging springs and is believed by the community as a form of gratitude to God. The purpose of this study describes the procession of the Iriban tradition and the value of mutual cooperation in the Iriban tradition as well as efforts to preserve the Iriban tradition in Lerep Village, West Ungaran District, Semarang Regency. This research uses a qualitative approach with data collection methods, namely observation, interviews and documentation as data collection techniques. The data analysis techniques go through the stages of data collection, data reduction, data presentation and conclusions. The research was conducted in a village precisely located in Lerep Village, West Ungaran District, Semarang Regency. The informants in this study were the Head of Lerep Village, Secretary of Lerep Village, Head of Tourism Awareness Group (Pokdarwis) Rukun Santoso, Elders and three Lerep Village communities. The results showed that the Iriban tradition is an annual tradition that is carried out on Kliwon Wednesday in the month of Sapar every year. The Iriban tradition is carried out by the people of Lerep Village every year on Wednesday Kliwon because it is an admonition from ancestors that is still followed by the community. The procession of the Iriban tradition is divided into two stages, namely the preparation and implementation stages. The preparatory phase includes Working Group meetings, preparation of the place of implementation of traditions and preparation of a place for cooking. While the implementation includes Kirab Iriban, Iriban Ritual, cooking, cleaning Wangan Cenginging, congratulations and eating together. The value of gotong in the Iriban tradition that can be interpreted and lived in the Iriban tradition is togetherness, unity, willing to sacrifice, help and socialization. The efforts to preserve the Iriban tradition are encouraged by the Village Government to involve the younger generation to participate directly through socialization to the younger generation and understanding from the community that the Iriban tradition is a form of gratitude and continues the tradition that has existed for generations